Application of the methodology of the 8 disciplines to reduce a non-compliance in a company in the automotive sector - Soligo, Lucas Pavani; Nunes, Deivid Marques (Brazilian Journal of Production Engineering, 2021)
This work aims to present the application of the structured methodology of the 8 disciplines (8D) for problem solving in a factory in the automobile industry. This non-conformity was analyzed using several tools and following the steps of the 8D methodology, the problem in question was detected in the transmission shaft straightening operation, due to a large increase in the crack index during the months of December 2020 and January 2021. For the preparation of this article, a case study was carried out, where all the data used were collected during the months of December 2020 until August 2021. After completing the 8 steps of the methodology, with all the analyzes carried out and actions implemented, it was found an efficient and effective corrective action for non-compliance, generating a reduction of approximately 96% in the crack rate.